2020
DOI: 10.1002/ccr3.3283
|View full text |Cite
|
Sign up to set email alerts
|

A Case of bilateral concomitant inguinal and femoral hernias treated with transabdominal preperitoneal repair

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There are only a few reports 6,7 of three or more hernias and only one case of four or more hernias. 4 To the best of our knowledge, this is the first case of four or more hernias on the same side.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…There are only a few reports 6,7 of three or more hernias and only one case of four or more hernias. 4 To the best of our knowledge, this is the first case of four or more hernias on the same side.…”
Section: Discussionmentioning
confidence: 79%
“…[1][2][3] Only Uesato et al reported a case of concurrent bilateral, inguinal, and femoral hernias among all instances of multiple hernias (four or more). 4 However, there are no previous reports about multiple hernias (four or more) on the same side. Thus, this case is the first of its kind.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation